Assistance In Preparing Financial Statements Based On MSME Accounting Standards At Wisata Halal Indonesia MSME - Darul Fahmi; Faizah Adisty; Rezi Eka Putra; Annisa Farida (Abdimas Paspama, 2023)
Limited knowledge of accounting and financial reporting remains a challenge for Micro, Small, and Medium Enterprises (MSMEs) in managing their businesses systematically and accountably. This community service program aimed to improve the knowledge and practical skills of Wisata Halal Indonesia MSME managers in recording business transactions and preparing financial statements based on accounting standards for MSMEs. The program was implemented through preliminary observation and interviews, online training, discussions, question-and-answer sessions, practical exercises, mentoring, and evaluation. The training involved ten participants consisting of administrative staff, supervisors, and the business owner. The materials covered basic accounting concepts, accounting processes, transaction recording, and practical preparation of balance sheets and income statements. Program evaluation was conducted qualitatively through participant engagement, discussions, question-and-answer sessions, and financial statement preparation exercises. The results showed that participants developed a better understanding of accounting processes and gradually improved their ability to prepare business financial statements. Participants also demonstrated active involvement throughout the training and practical sessions. The program indicates that accounting training combined with practical assistance can strengthen MSME financial reporting capabilities and support more systematic, transparent, and accountable financial management. Continuous mentoring is recommended to ensure the consistent application of accounting practices in daily business activities.